2004
DOI: 10.1111/j.1399-0012.2004.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic donor nephrectomy vs. open live donor nephrectomy: a quality of life and functional study

Abstract: The results of this study support the decisions of many kidney transplant centers to adopt LDN programs as standard of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 5 publications
4
45
0
1
Order By: Relevance
“…Studies were from 19 countries; most were conducted in the United States (43% of studies) followed by Germany (10%), Canada (6%), India (4%), Sweden (4%), Australia (4%), the Netherlands (4%) and Switzerland (4%). During follow-up, 46 studies assessed the physical health of donors (29)(30)(31)(32)(33)(34)(35)(36)38,(40)(41)(42)(43)(44)(45)(46)(48)(49)(50)(51)(53)(54)(55)(56)(57)(58)(59)(60)(61)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79) and 26 reported that some donors had faced graft failure or recipient death (29,(31)(32)…”
Section: Description Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies were from 19 countries; most were conducted in the United States (43% of studies) followed by Germany (10%), Canada (6%), India (4%), Sweden (4%), Australia (4%), the Netherlands (4%) and Switzerland (4%). During follow-up, 46 studies assessed the physical health of donors (29)(30)(31)(32)(33)(34)(35)(36)38,(40)(41)(42)(43)(44)(45)(46)(48)(49)(50)(51)(53)(54)(55)(56)(57)(58)(59)(60)(61)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79) and 26 reported that some donors had faced graft failure or recipient death (29,(31)(32)…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Some reported outcomes for a select subgroup of donors, such as those where the recipient was still alive (51) or where donors were parents to recipient children who were of minor age (42,73,75). Ten compared the outcomes of laparoscopic donors to those who received an open nephrectomy (50,53,57,60,62,66,(75)(76)(77)79) and one compared the outcomes of donors who underwent two different open procedures (69).…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations